Analysis of sequence variations of Calpastatin gene of inhibitory region in Cyprinus carpio var. communis - Mir, Dr Mohammed Iqbal; Khan, Salma; Shah, F A; Bhat, F A; Lone, Gh Nabi; Balkhi, Masood H (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Calpastatin gene, an endogenous inhibitor of calpain enzyme, is important for maintaining muscle texture and postmortem degradation of myofibrils.Â Present study was carried out for the identification of SNPs in the inhibitory region of calpastatin gene in common carp Cyprinus carpio var. communis for genetic improvement of genotypes. Primers were designed from cDNA sequences of Atlantic salmon (AFV08638.1), Rainbow trout (NP_001118010.1) and cDNA as well as genomic DNA sequences of Zebra fish (NM_001130591.2) to amplify the CAST gene in Common carps. Four exons (13, 14, 19 and 20) and intervening introns demarcated by zebrafish genomic data base of 316 and 311 base pairs were amplified. The sequencing and insilico translation was done for the identification and characterization calpastatin. The results showed that Cyprinus carpio var. communis have two highly conserved sequence motifs DTLPP, GYR repeats in the inhibitory domain which corresponds to the exon-14 and exon-20 of Zebra fish. The single amino acid change in the inhibitory motif G (GGT)/X (X = Q 394aa (CAA) in Danio rio, Sequence ID: ref|NP_001124063.2, E 491aa (GAG) in Salmo salar, Sequence ID: ref|NP_001167162.1, K 223aa (AAG) in Onchorhyncus mykiss long isoform, Sequence ID: ref|NP_001118010.1, and E 54aa (GAG) in Onchorhyncus mykiss short isoform, Sequence ID: ref|NP_001118117.1) have role in the diversification of inhibitory activity of the protein due to species diversification. Another interesting characteristic feature of the inhibitory motif of exon-20 in Common carps having Glysine (GGT) amino acid and rest instead of Glutamic acid (GAG) at 548th aa in Danio rio and 689th aa Salmo salar. It was also observed that Common carp shear (94-95%) CAST gene sequence with Zebra fish while as only (52-54%) sequence homology was observed with Atlantic salmon and Rainbow trout due to species divergence. Phylogenetic analyses of different species revealed telosts are more primitive than tetrapods. Variations observed in inhibitory domain play important role in postmortem proteolysis. Development of markers for meat tenderness and fillet quality based on the mutations in the inhibitory region will help in selecting genotypes of better fillet/texture quality.